SISTEM MANAJEMEN ARSIP TERPADU BERBASIS MOBILE ANDROID DALAM MENUNJANG EFESIENSI KERJA PT. KRAKATAU STEEL - Asep Mabrur A'id; Anita Megayanti (Teknik Informatika Fakultas Ilmu Komputer, 2020)
Archive Management System can be interpreted as a process of managing archives / documents that no longer use manual methods, but by applying technology to support activities to speed up the process of processing data into information, access to information quickly, and accurately as well as safeguarding more document storage well. In order to create an integrated archive management, an analysis and control of a policy will be made in a decision before being circulated or distributed to the relevant institutions / institutions to withdraw the document because it is invalid / expired due to a new decision replace it. PT. Krakatau Steel is currently based on mobile not yet running optimally at every stage of archive management based on Mobile. This is influenced by several factors, namely not yet integrated systems, volume of archives, human resources, and facilities.Each organization must have an archival unit as a work unit that manages archives / documents and is responsible for the existence of archives / documents, security, control and control of archives / documents, having and updating databases and processing data and information. The process of integrated archive management system based on Android mobile (dynamic or static, electronic or non-electronic) can be done more effectively so that it helps in supporting the work efficiency of the employees of PT. Krakatau Steel. SMART (Integrated Archive Management System is a web-based filing application program that is designed to manage archives as a whole starting from the correspondence function, inputting list of dynamic & static archive information, searching & borrowing archives, archive transfer, and archive shrinkage that can be integrated with all PT Krakatau Steel's work unit.